2019
DOI: 10.1111/ajt.15148
|View full text |Cite
|
Sign up to set email alerts
|

Induction immunosuppression agents as risk factors for incident cardiovascular events and mortality after kidney transplantation

Abstract: Low T cell counts and acute rejection are associated with increased cardiovascular events (CVEs); T cell–depleting agents decrease both. Thus, we aimed to characterize the risk of CVEs by using an induction agent used in kidney transplant recipients. We conducted a secondary data analysis of patients who received a kidney transplant and used Medicare as their primary insurance from 1999 to 2010. Outcomes of interest were incident CVE, all‐cause mortality, CVE‐related mortality, and a composite outcome of morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…2 Remarkably, gene expression profiling indicates that acute and chronic rejection share similarities in activation of IFN-g, TNF-a, or other cytokines, chemokines, and receptors. 2,3 To control lymphocyte-dependent allograft rejection, therapeutic targets include ILs (eg, IL-2, -4, -6, -12/ 23, and -15) 1,4 and chemokines, 5 whereas controlling innate responses needs additional strategies. 6 Transplanting allogeneic cells or tissues is highly significant for liver-directed therapies.…”
mentioning
confidence: 99%
“…2 Remarkably, gene expression profiling indicates that acute and chronic rejection share similarities in activation of IFN-g, TNF-a, or other cytokines, chemokines, and receptors. 2,3 To control lymphocyte-dependent allograft rejection, therapeutic targets include ILs (eg, IL-2, -4, -6, -12/ 23, and -15) 1,4 and chemokines, 5 whereas controlling innate responses needs additional strategies. 6 Transplanting allogeneic cells or tissues is highly significant for liver-directed therapies.…”
mentioning
confidence: 99%
“…Impaired GLS in CKD patients is an indicator of decreased LV contractility probably due to LV remodelling with increased accumulation of extracellular matrix and myocardial fibrosis. Recently, Sandal et al found that congestive heart failure, but not the coronary artery disease, is the most common cause of cardiovascular events following KTx [9]. That finding confirms earlier outcomes of studies based on the United States Renal Data System conducted on thousands of patient [10].…”
Section: Discussionmentioning
confidence: 60%
“…Impaired GLS in CKD patients is an indicator of decreased LV contractility probably due to LV remodelling with increased accumulation of extracellular matrix and myocardial fibrosis. Recently, Sandal et al found that congestive heart failure, but not coronary artery disease, is the most common cause of cardiovascular events following KTx [11]. That finding confirms earlier outcomes of studies based on the United States Renal Data System conducted on thousands of patient [12].…”
Section: Discussionmentioning
confidence: 61%